Halopriming and Hydropriming Treatments to Overcome Salt and Drought Stress at Germination Stage of Corn (Zea mays L.) - Hamid Abbasdokht; Ahmad Gholami; H. Asghari (Desert, 2014)
To study the effects of halopriming and hydropriming in overcoming salt and drought stress in corn (Zea mays L.),two experiments were separately conducted at Shahrood University of Technology. Seed treatments consisted ofcontrol (untreated seeds), soaking in distilled water for 32 h (hydropriming), and soaking in 50 mmol solution ofCaCl2 for 16 h (halopriming). Germination and early seedling growth were studied using distilled water (control) andosmotic potentials of -0.4, -0.8, and -1.2 MPa from NaCl (salinity stress) and polyethylene glycol [PEG 6000(drought stress)]. Results showed that in both salinity and drought experiments, germination percentage reducedsignificantly according to decreased osmotic potential. Hydroprimed and haloprimed seeds achieved the minimumreductions in germination percentage. The maximum reduction in germination percentage was recorded fromuntreated seeds (control). Minimum reduction percentages of root length (RPL root) and shoot length (RPL shoot)were attained from hydroprimed and haloprimed seeds due to NaCl and PEG conditions (-0.4 MPa), and maximumRPL root and RPL shoot were attained from controlled seeds due to NaCl and PEG (-1.2 MPa) conditions. Thereduction percentage of dry weight for root (RPD root) and shoot (RPD shoot) increased according to increasedosmotic potential in both NaCl and PEG, but RPD for shoot was significantly affected compared with RPD for root.Interaction of seed priming treatment and osmotic potential for the germination index (GI) showed that under 0 and -0.4 MPa, hydroprimed and haloprimed seeds had higher GI as compared with untreated seeds due to NaCl and PEGconditions. Interaction between the seed priming treatment and osmotic potential significantly affected the vigourindex (VI) due to NaCl and PEG conditions, and halopriming significantly increased VI at high osmotic potentials.On average, the VI of haloprimed seeds was higher than that of untreated seeds at high osmotic potentials and wasnot significantly different from hydroprimed and untreated seeds at low osmotic potentials. It is concluded that undersalinity stress, the osmotic effect is more important than the toxic effect in loss of seed germination. Moreover,hydropriming practically ensured rapid and uniform germination with few abnormal seedlings.